Determinants of Health Status Three to Six Years After Surgical Treatment of Closed Ankle Fracture and Comparison with the General Population: A Historical Cohort Study. Issue 3 (28th September 2017) - Stavem, Knut; Naumann, Markus G.; Sigurdsen, Ulf; Utvåg, Stein Erik
Abstract : Background: The purposes of the present study were to identify the determinants of health status 3 to 6 years after open reduction and internal fixation (ORIF) for the treatment of closed ankle fracture and to compare the health status of patients who had undergone this procedure with that in the general population after adjusting for sociodemographic variables, body mass index (BMI), and smoking status. Methods: The present study was a historical cohort study combined with a postal survey. In total, 1, 149 patients who underwent ORIF for the treatment of closed ankle fractures at 2 hospitals were eligible for chart review; 959 with low-energy fractures were eligible for a postal survey, and 471 (49%) responded to the Short Form Health Survey-36 (SF-36) health status questionnaire and provided data on BMI. Determinants of the physical functioning (PF), physical component summary (PCS), and mental component summary (MCS) scores of the SF-36 were analyzed by means of multivariable linear regression analysis. The health status of patients with an ankle fracture (n = 471) was compared with that in a sample of the general population (n = 5, 396) by means of multivariable regression. Results: Age, American Society of Anesthesiologists (ASA) class III, and complications following surgery were associated with PF and PCS scores, and a BMI of ≥30 kg/m 2 and current smoking status was associated with PF and MCS scores. However, the PF, PCS, and MCS scores of patients with ankle fractures did not differ from those of the general population, with unstandardized regression coefficients of 0.25 (95% confidence interval [CI], –1.67 to 2.16; p = 0.80), 0.67 (95% CI, –0.35 to 1.70; p = 0.199), and –0.57 (95% CI, –1.63 to 0.49; p = 0.29), respectively. Conclusions: Age, ASA class III, and complications following surgery were associated with PF and PCS scores at 3 to 6 years after surgery for the treatment of closed ankle fractures. However, the health status of patients with ankle fractures did not differ from that in the general population after adjusting for differences in demographic variables, BMI, and smoking status. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.